Disaster Management and Mitigation Practices of Schools Basis for A Proposed Project Salba Bida (Strategies and Approaches in Leading Basic Actions In Building Integrated Disaster Awareness) - Manzano, Vergilio (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the disaster management practices of public schools in Legislative District III of Isabela Province and served as the basis for the development of the SALBA BIDA framework for strengthening disaster resilience in educational institutions. Anchored on the Community of Practice Theory, Organizational Change Theory, Needs Assessment Theory, and Program Evaluation Theory, the study examined disaster management practices in terms of safe learning facilities, school disaster management, and disaster risk reduction in education. A mixed-methods research design was employed, combining quantitative and qualitative approaches. Data were collected from 100 purposively selected school administrators, School Disaster Risk Reduction and Management (DRRM) coordinators, and administrative officers through a structured questionnaire and semi-structured interviews. Quantitative data were analyzed using descriptive statistics, the Kruskal-Wallis H Test, Mann-Whitney U Test, and Kendall Tau Coefficient. Findings revealed that schools generally demonstrated high compliance in maintaining safe learning facilities, implementing school disaster management systems, and integrating disaster risk reduction in education. Strong performance was observed in safety measures, preparedness activities, communication systems, documentation, coordination, and community engagement. However, financial constraints emerged as the most significant challenge, while technical and human-related concerns were only slightly encountered. Significant differences in disaster management practices were observed according to school type, school size, and School-Based Management (SBM) level, with schools exhibiting more developed institutional systems demonstrating stronger preparedness and management practices. The study concluded that disaster management practices were generally evident across schools but require continuous improvement in preparedness programs, infrastructure, resource allocation, and stakeholder capacity-building. Enhanced policy implementation, regular training initiatives, and stronger collaboration with disaster risk reduction agencies are recommended to further strengthen school resilience. The study supports SDG 4 (Quality Education), SDG 11 (Sustainable Cities and Communities), SDG 13 (Climate Action), and SDG 17 (Partnerships for the Goals). Its sustainability contribution lies in promoting educational continuity, institutional resilience, effective governance, community engagement, and long-term disaster risk reduction in educational settings.